Race matters: public views on sentencing - Singh, Anne-Marie (Canadian journal of criminology and criminal justice, 2017)
Research consistently finds that while the public expresses concerns about sentence leniency in the abstract, when presented with a specific case, people are typically not particularly punitive (Hough and Roberts 2012). While Canadian studies have further explored the effect of various social-structural factors on sentencing preferences, absent is any empirical investigation of the role, if any, that the offender's ethnicity plays. We explore this question using a convenience sample of adult Canadians and four vignettes (of an armed robbery), which were identical except for the racialized identity of the offender. Respondents' sentencing choices and perceptions of offender dangerousness, culpability, and recidivism risk were elicited. Results revealed that the ''black'' offender was rated as being significantly more dangerous than the ''white'' offender and also received a significantly more punitive sentence. After controlling for the impact of the criminal record and views of dangerousness, culpability, and recidivism risk, there was still an independent, albeit very small, effect of the racialized identity of the offender on sentencing preferences. The strongest predictor of the sentence, however, was how dangerous respondents viewed the offender. Part of the desire for a harsher sentence for the black offender likely related to views of dangerousness. The implications of these findings are discussed.